2015
DOI: 10.1179/2042349715y.0000000002
|View full text |Cite
|
Sign up to set email alerts
|

What is the origin of the Scottish populations of the European endemicCherleria sedoides(Caryophyllaceae)?

Abstract: This version available http://nora.nerc.ac.uk/510777/ NERC has developed NORA to enable users to access research outputs wholly or partially funded by NERC. Copyright and other rights for material on this site are retained by the rights owners. Users should read the terms and conditions of use of this material at http://nora.nerc.ac.uk/policies.html#access This document is the author's final manuscript version of the journal article, incorporating any revisions agreed during the peer review process. Some diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…More detailed work on two species of the group provided evidence for hybridization. A study of C. sedoides L. [ 57 , 84 ] showed high chloroplast DNA (cpDNA) haplotype and nrDNA ribotype diversity throughout its wide range (including the Alps, the Balkan Peninsula, the Pyrenees, and Scotland). It also showed that the most common cpDNA haplotype clade most likely originated through hybridization of C. sedoides with an extinct species of the genus [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…More detailed work on two species of the group provided evidence for hybridization. A study of C. sedoides L. [ 57 , 84 ] showed high chloroplast DNA (cpDNA) haplotype and nrDNA ribotype diversity throughout its wide range (including the Alps, the Balkan Peninsula, the Pyrenees, and Scotland). It also showed that the most common cpDNA haplotype clade most likely originated through hybridization of C. sedoides with an extinct species of the genus [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…More detailed work on two species of the group provided evidence for hybridization. A study of C. sedoides L. (Valtueña et al 2015, Moore et al 2017 showed high chloroplast DNA (cpDNA) haplotype and nrDNA ribotype diversity throughout its wide range (including the Alps, the Balkan Peninsula, the Pyrenees, and Scotland). It also showed that the most common cpDNA haplotype clade most likely originated through hybridization of C. sedoides with an extinct species of the genus (Moore et al 2017).…”
Section: Introductionmentioning
confidence: 99%